Transforming Graduate Quality: The Strategic Power of Visionary Leadership in Islamic Secondary Education - Ilham Martua Hasibuan; Budi (Al-Qalam Institue, 2026)
This study aims to analyze the role of visionary leadership in improving graduate quality, identify strategies for integrating institutional vision into quality improvement programs, and examine the supporting and inhibiting factors affecting their implementation. A qualitative descriptive approach was employed, with data collected through observations, in-depth interviews, and document analysis. The data were analyzed using the processes of data reduction, data display, and conclusion drawing, while source and technique triangulation were applied to ensure trustworthiness. The findings reveal that visionary leadership is effectively implemented through participatory vision formulation, consistent communication of institutional goals, and the development of academic, character-building, and religious programs aligned with quality improvement objectives. Effective strategies include integrating the institutional vision into educational practices, empowering teachers, fostering collaboration with stakeholders, and implementing continuous monitoring and evaluation. The study also identifies teacher competence, stakeholder support, and adequate facilities as enabling factors, while limited student motivation, insufficient parental involvement, and rapid technological changes remain key challenges. These findings imply that visionary leadership is essential for fostering a sustainable quality culture and strengthening institutional capacity to produce competitive graduates in a dynamic educational environment.